Resident Attitudes towards gaming and Tourism Development in Macao: Growth Machine Theory as a Context for Indentifying Supporters and opponents - Harrill, R.; Uysal, Muzaffer; Cardon, P.; Vong, F.; Leonarda, D. (John Wiley & Sons, 2011)
Despite global recession, Macao continues to develop as an international gaming destination. However, as the intensity of development increases, the government is losing support for the gaming industry among some residents. This loss of support may be examined within the context of growth machine theory. This paper surveys residents regarding their attitudes towards gaming and development. The findings suggest residents can be divided into two groups — gaming supporters and gaming opponents. From these findings, recommendations are made for future planning, development and marketing in Macao. Copyright © 2010 John Wiley & Sons, Ltd.